Interaction a construction with the other - Gutierrez Rodriguez, Elizabeth; Lourdes Rodriguez, Maria; Vargas Becerra, Mayerly (Rastros Rostros, 2023)
The school as a center of integral formation must assume the commitment to implement day by day new strategies and proposals that promote the formation of autonomous, reflective learners with a constructive critical spirit and ethical principles capable of facing the multiple challenges that the modern world proposes.